Shifting Meridians: US authorship in world literary space - Leypoldt, Günter (American literary history, 2015)
Based on a comparison of Pascale Casanova's The World Republic of Letters (1999) and Mark McGurl's The Program Era (2009), this essay explores how the study of literary institutions can help us understand the recent shifts of literary values in the US and the world. Reading Edith Wharton's novella “False Dawn,” I will discuss the relevance of material networks for world-literary space. I will then look at how the cultural-expression models of literature we owe to the “Herder effect” (Casanova) relate to the value hierarchies of the global and local literary fields: Baudelaire's reading of Edgar Allan Poe and the post-1960s rise of “high-cultural pluralism” (McGurl) will serve as examples here. A third section will refer to the Jonathan Franzen–Oprah Winfrey controversy to argue that distinguishing between sacralized and quotidian literary economies helps us to resolve some of the classic paradoxes of cultural authority (the feeling that literary meridians are either undemocratic or rendered obsolete by a commercialized literary marketplace). Finally, I will trace the shifting meridians of world literary space with a comparative reading of Henry James’s The Ambassadors (1903) and Ben Lerner's Leaving the Atocha Station (2011).